PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER) DAN TOTAL ASSET TURN OVER (TATO) TERHADAP RETURN ON ASSET (ROA) PADA PERUSAHAAN PT ERAJAYA SWASEMBADA TBK PERIODE 2011-2023 - Alif Farhan Ramadhan; Riski Dwi Nugroho (CV. Denasya Smart Publisher, 2025)
This study aims to determine the effect of Current Ratio, Debt to Equity Ratio and Total Asset Turn Over on Return On Asset at PT Erajaya Swasembada Tbk for the period 2011 - 2023 simultaneously and partially. The method used is an associative descriptive method with a quantitative approach. The population in this study used the financial statements of the company PT Erajaya Swasembada Tbk for the period 2011-2023. The data analysis technique used is financial ratio analysis, descriptive statistical analysis, statistical analysis through the calculation stages of SPSS using IBM SPSS version 26. Classical assumption test (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), multiple linear regression test, hypothesis testing (partial T test and simultaneous F test), R2 determination coefficient test. The results of data processing simultaneously show that CR, DER and TATO have a positive and significant effect on ROA with a calculated F value of 6.849> F table 3.86 with a significance level of 0.011 <0.05. From the partial test, CR has a significant effect on ROA with a T value of 3.209> T table 2.2621 with a significance level of 0.011 <0.05. DER has no significant effect on ROA with a T value of 1.518 < T table 2.2621 with a significant level of 0.163 > 0.05. TATO has a significant effect on ROA with a T value of 2.794 > T table 2.2621 with a significant level of 0.021 <0.05. Based on the coefficient of determination test R2 square of 0.594 or 59.4%. It can be concluded that the contribution of CR, DER and TATO to ROA is 59.4% while 40.6% is influenced by other variable not examined in this study